Daqu microbiota exhibits species-specific and periodic succession features in Chinese baijiu fermentation process. (September 2021) - Xiao, Chen; Yang, Yang; Lu, Zhen-Ming; Chai, Li-Juan; Zhang, Xiao-Juan; Wang, Song-Tao; Shen, Cai-Hong; Shi, Jin-Song; Xu, Zheng-Hong
Abstract: Daqu, a brick-shaped product spontaneously fermented under an open environment, has been regarded as the starter of fermentation, raw enzyme preparation and raw materials for baijiu production. However, its contribution in baijiu fermentation has not been fully elaborated yet. Here, the effects of daqu microbiota on baijiu fermentation were investigated under both field-scale and lab-scale conditions. In field-scale baijiu fermentation, the dominant daqu microbes (average relative abundance>10.0%), including unclassified_ Leuconostocaceae, Thermoascus, and Thermomyces, tended to dominate the early stage (0–7 d). However, the rare daqu microbes (average relative abundance <0.1%, e.g., Kazachstania ) tended to dominate the middle and late stages (11–40 d). In addition, some genera showed differences in species diversity between daqu and fermented grains. The average relative abundance of Lactobacillus was over 75% during baijiu fermentation, and most of them were affiliated with Lactobacillus acetotolerans, while Lactobacillus crustorum dominated the Lactobacillus OTUs in daqu . The similar patterns were also observed during lab-scale baijiu fermentation. The results of function prediction showed the enriched metabolic pathways were associated with glycolysis and long-chain fatty acid esters in baijiu fermentation. These results improved the understanding of daqu microbiota function during baijiu fermentation and provided a basic theory to support the regulation of baijiu production. Graphical abstract: Image 1 Highlights: Microbiota succession of daqu during alcohol fermentation were studied. The dominant species of Lactobacillus in fermented grains were different from daqu. The dominant and rare daqu microbes respectively dominated the early and late stages of alcohol fermentation.